Retinopathy of Prematurity: Incidence, Risk Factors & Outcome in North Indian Rural and Semi-urban population - Parihar, Kamal; Kumar Gupta, Pradeep; Singh, Vandana; Sharma, Sanjay (Journal of Nepal Paediatric Society, 2022)
Introduction: ROP is a challenge due to better premature survival. It has an increasing trend and is a preventable cause of vision loss. Its occurrence, severity and outcome in rural population is poorly studied. Methods: Ahospital based prospective observational longitudinal study was conducted on babies born at a tertiary care centre. Babies with gestation <32 weeks or birth weight < 1500 g were screened for ROP. Preterm babies of >32 weeks gestation with oxygen requirement, RDS, surfactant use, PDA, neonatal hyperbilirubinemia requiring phototherapy, septicemia, red cell transfusion due to anemia, need for inotropes were also included. Babies with ROP were assessed for severity as also need for intervention and were followed for12 months. Results: Of the 211 neonates screened, 51 had ROP. Frequency was inversely related to both birth weight and gestational age with no gender difference. Oxygen therapy (p 0.001), RDS (p 0.005), mechanical ventilation (p0.003) and septicemia (p 0.005) were main risk factors. Neonatal hyperbilirubinemia requiring phototherapy was found to be protective (p 0.0005). 15.68% cases required laser photocoagulation. During follow up, ROP regressed in all patients. Conclusions: Risk factors for ROP included oxygen usage, RDS, mechanical ventilation and septicemia. Blood products or inotropes use was not an independent factor. Neonatal hyperbilirubinemia was protective. When diagnosed early, outcome is good in ROP.